Cartografía comparada de la desinformación política en Iberoamérica: los casos de Argentina y España. - Renedo-Farpón, Cristina (2025)
In the current Ibero-American context, marked by growing polarization, political disinformation has intensified through speeches delivered by political leaders on social media, in the press, and in institutional settings. This research analyzes 466 messages identified as disinformation in 2023 by Chequeado (Argentina) and Newtral (Spain), coinciding with national elections in both countries. A mixed-methods approach is applied, based on content analysis, considering the type of disinformation, topics, dissemination channels, and the classification provided by the fact-checking agencies. The findings reveal similarities in the most frequent themes and types of informational disorder, but also differences in the platforms used to spread disinformation. A significant presence of misleading messages in institutional and media contexts is particularly notable, highlighting the direct involvement of political actors in disinformation and its impact on the public agenda, especially in a scenario of rising far-right parties.